The Pain-Depression Dyad and the Association with Sleep Dysfunction in Chronic Rhinosinusitis - Cox, Daniel R. (Int Forum Allergy Rhinol, 2016)
BACKGROUND: Depression, pain, and sleep disturbance is a symptom cluster often found in patients suffering from chronic illness, exerting a large impact on quality-of-life (QOL). A wealth of literature exists demonstrating a significant association between depression, pain, and sleep dysfunction in other chronic diseases. This relationship has not been described in patients with chronic rhinosinusitis (CRS). METHODS: Sixty-eight adult patients with CRS were prospectively enrolled. Patients at risk for depression were identified using the Patient Health Questionnaire-2 (PHQ-2) using a cutoff of 1 or greater. Pain experience was measured using the Brief Pain Inventory Short Form (BPI-SF) and the Short Form McGill Pain Questionnaire (SF-MPQ). Sleep quality was assessed using the Pittsburgh Sleep Quality Index (PSQI). RESULTS: Forty-seven patients were at risk for depression. Significant positive correlations were found between total PSQI scores and all pain measures (R=0.38–0.61, p≤0.05) and between total PSQI scores and PHQ-2 scores (R=0.46, p<0.05). For patients at risk for depression, significant, positive correlations were found between pain measures, the total PSQI score, and the three PSQI subdomains (sleep latency, sleep quality, and daytime dysfunction; R=0.31-0.61, p<0.05). The relationship between pain and sleep dysfunction scores was not seen in the absence of depression. CONCLUSIONS: Depression, pain, and sleep dysfunction are inter-related in patients with CRS. In the absence of depression significant correlations between pain and sleep are not observed, suggesting that depression plays a key role in this interaction. Further research investigating the complex relationship between depression, pain, and sleep dysfunction in CRS is needed.